Effects of glycyrrhizin on the pharmacokinetics of paeoniflorin in rats and its potential mechanism - Hongjuan Sun; Jingfeng Wang; Juan Lv (Taylor & Francis Group, 2019)
Context: Paeoniflorin is reported to possess numerous pharmacological activities. Paeoniflorin and glycyrrhizin are always used together for the treatment of disease in China clinics; however, the drug-drug interaction between glycyrrhizin and paeoniflorin is still unknown. Objective: This study investigates the effects of glycyrrhizin on the pharmacokinetics of paeoniflorin in rats. Materials and methods: The pharmacokinetics of orally administered paeoniflorin (20 mg/kg) with or without glycyrrhizin pre-treatment (at a dose of 100 mg/kg/day for 7 days) were investigated in male Sprague-Dawley rats using LC-MS/MS. Additionally, Caco-2 cell transwell model and rat liver microsome incubation experiments were also conducted to investigate its potential mechanism. Results: The results showed that when the rats were pre-treated with glycyrrhizin, the Cmax of paeoniflorin decreased from 59.57 ± 10.24 to 45.36 ± 8.61 ng/mL, and AUC0-inf also decreased from 282.02 ± 35.06 to 202.29 ± 28.28 μg·h/L. The t1/2 value of paeoniflorin decreased from 8.48 ± 2.01 to 5.88 ± 1.15 h (p < 0.05). The Caco-2 cell transwell experiments indicated that glycyrrhizin could increase the efflux ratio of paeoniflorin from 2.71 to 3.52, and the rat liver microsome incubation experiments showed that glycyrrhizin could significantly increase its intrinsic clearance rate from 53.7 ± 4.6 to 85.6 ± 7.1 μL/min/mg protein. Conclusions: These results indicated that glycyrrhizin could affect the pharmacokinetics of paeoniflorin, and it might work through decreasing the absorption of paeoniflorin by inducing the activity of P-gp or through increasing the clearance rate in rat liver by inducing the activity of CYP450 enzyme.